Ultrasound-guided axial facet joint interventions for chronic spinal pain: A narrative review - Michael J. Wong; Manikandan Rajarathinam (Taylor & Francis Group, 2023)
ABSTRACTBackground Axial facet joint interventions (e.g., medial branch block and radiofrequency ablation, facet joint intra-articular injection) are commonly performed for managing chronic spinal pain. Although traditionally performed with fluoroscopy or computed tomography (CT) guidance, ultrasound-guided techniques have also been developed for these interventions.Aims The aim of this study is to present contemporary ultrasound-guided techniques for facet joint interventions and synthesize data addressing their accuracy, safety, and efficacy.Methods The PubMed, MEDLINE, CINAHL, Embase, and Cochrane Central Register of Controlled Trials databases were systematically searched for studies of ultrasound-guided facet joint interventions with human subjects from November 1, 1992, to November 1, 2022. Additional sources were drawn from reference lists and citations of relevant studies.Results We found 48 studies assessing ultrasound-guided facet joint interventions. Ultrasound guidance for injection of the cervical facet joints and their innervating nerves had favorable accuracy (78%-100%), with lower procedural time compared to fluoroscopy or CT guidance and comparable pain relief. Accuracy with ultrasound-guided lumbar facet joint intra-articular injection (86%-100%) was more reliable than medial branch block (72%-97%); analgesia was comparable to fluoroscopy and CT guidance. In general, these procedures were more challenging for patients with obesity, and deeper structures were more difficult to accurately target (e.g., lower cervical levels, L5 dorsal ramus).Conclusions Ultrasound-guided facet joint interventions continue to evolve. Some technically challenging interventions may be impractical for widespread usage or require further technical refinement. The utility of ultrasound guidance with obesity and abnormal anatomy may be reduced.